Impact of climate change on precipitation in Suriname - Smit, Jacob (author) (2023)
Suriname is highly vulnerable to hazards that are climate change related, such as droughts and floods. Knowledge about future precipitation in Suriname is needed for the population of Suriname in order to adapt to climate change effects. By analysing 32 CMIP6 models, this study investigates the impact of climate change on precipitation in Suriname. The intermodel spread of the projected change in precipitation in 2100 compared to the reference period (1991-2020) is large, ranging from -45% (-2.0 mm/day) to +10% (+0.5 mm/day). Drivers of climate change in Suriname are the Intertropical Convergence Zone (ITCZ), Atlantic Meridional Overturning Circulation (AMOC) and EL Niño Southern Oscillation (ENSO). A weaker AMOC strength leads to warming of the south Atlantic Ocean and cooling of the north Atlantic Ocean, indicating a southward shift of the ITCZ. More El Niño like conditions lead to weakening of the mean zonal circulation along the equator and an eastward migration of the Walker Circulation in the Pacific. The occurrence of an increase in upward motion over the Pacific ITCZ and an increase in downward motion over Suriname also indicate an eastward migration of the Walker Circulation. With an eastward migrated Walker circulation an upward motion of moisture is strengthened and deep convection is increased over the Pacific. At the same time the opposite happens in Suriname where deep convection is decreased due to downward motion of air. Models with relatively high future drying project the ITCZ at a more southward position, leading to low precipitation amounts in Suriname. Next to that, these models project a relatively stronger southward shift of the ITCZ compared to wet models, leading to an even stronger drying effect in Suriname. The climate models show a mean weakening of the AMOC strength, especially the dry models. More El Niño like conditions, with a decrease in deep convection in projections from dry models, are another reason for lower precipitation projections for dry models than for wet models. After ...